(3JMaI GdRGFQ aj RjGQI GdfHj hGdCFeI GdWGgQjfs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj, J (B1111(3g`s
(3ChdgG (B:s
(3HSe Gddg hHGddg hdG Mhd hdG bhI EdG HGddg(B... (3Gddge WQg Hg bdHj hGTQM Hg UOQj(B...s
(3BNQgG (B:s
(3hGMTQfG aj ReQI ef bGd dG Edg EdG Gddg eMeO QShGd Gddgs
(3HOGNdgG JQLeI HGdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B48s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B154s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B249s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs